An improved shear deformable theory for bending and buckling response of thin-walled FG sandwich I-beams resting on the elastic foundation. (15th December 2020) - Nguyen, Ngoc-Duong; Vo, Thuc P.; Nguyen, Trung-Kien
Abstract: This paper proposes an improved first-order beam theory by separation of variables for bending and buckling analysis of thin-walled functionally graded (FG) sandwich I-beams resting on a two-parameter elastic foundation. By dividing the displacements into bending and shear parts, this model can produce the deflections for both two cases with and without shear effect. The mechanical properties of beams based on the power law distribution of volume fraction of ceramic or metal. Governing equations are established from Lagrange's equations. The new Ritz's approximation functions, which are combined between orthogonal polynomial and exponential functions, are proposed to solve problem. The deflections and critical buckling loads of thin-walled FG sandwich I-beams are presented and compared with those available literature to verify the present theory. The effects of material distribution, boundary conditions, length-to-height ratio, shear deformation and foundation parameters on the results are investigated in detail.